Antimicrobial combined action of Mentha pulegium, Ormenis mixta and Mentha piperita essential oils against S. aureus, E. coli and C. tropicalis: Application of mixture design methodology. (June 2021) - Chraibi, Marwa; Fadil, Mouhcine; Farah, Abdellah; Lebrazi, Sara; Fikri-Benbrahim, Kawtar
Abstract: Experimental design methodology (mixture design) coupled to microdilution assay were used to study the potential interactions between several active compounds from three Moroccan essential oils (EOs) (M. pulegium, O. mixta and M. piperita) against S. aureus E. coli and C. tropicalis, to increase their sensitivity and to predict optimal formulations. EOs extraction was firstly obtained by hydrodistillation, then, their chemical composition was determined by GC/MS and their antimicrobial activity was evaluated. The optimization of antimicrobial activity of essential oils mixtures by augmented simplex-centroid design allowed us to model and validate statistically as well as to establish a prediction profile of the studied phenomena. The optimization of mixtures antimicrobial activities has highlighted the synergistic effect between M. piperita and M. pulegium essential oils. The optimal mixture predicted against E. coli, S. aureus and C. tropicalis corresponded to 54%/46%; 56%/44% and 55%/45% of M. piperita and M. pulegium essential oils, respectively. This study shows that the combination of essential oils may be applicable in the fight against emerging microbial drug resistance or useful as natural food preservatives. Graphical abstract: Image 1 Highlights: Antibacterial activity of three essential oils was tested alone and in combination. Optimal formulation for all studied strains was identified by mixture design. Synergistic effect between essential oils was highlighted. Hight synergy was observed for M. piperita/M. pulegium essential oils combination.